054 The individual costs of multiple sclerosis. Issue 6 (27th May 2022) - Nicholas, R; Middleton, R; Tuite-Dalton, K; Rogers, W; Craig, E; Chevli, M; Pulikottil-Jacob, M; Heaven, M
Abstract : Background: The UK Multiple Sclerosis Register (UKMSR) captures data from multiple sources including directly from people with MS (pwMS) via online questionnaires. There is little research into the non-medical (personal) costs of MS. In partnership with Sanofi we investigated healthcare resource use and costs (excluding drugs), including who bears these costs, by disease severity and type Methods: A cost of illness questionnaire was deployed to 3035 pwMS on the UKMSR. Respondent's answers were linked to retrospective UKMSR data. Resource consumption was categorised as being direct (medical) or indirect (non-medical) and costed by NHS and Social Services estimates for 2018. Results: £509, 003 was calculated as non-medical costs over a year and £435, 488 in medical costs generated over 3 months (n=537, 6935 interventions). PwMS reported self-funding 75% of non-medical costs these were mainly home modifications. Costs, increased with disability but those with indirect costs (n=138) had higher medical costs, were more disabled and were more likely to be unemployed than those with medical interventions only (n=399). Conclusions: The importance of disability in driving costs is again clearly illustrated with balance between indirect and direct costs consistent with the UK health environment as a whole. PwMS and their families fund 75% of non-medical costs that can facilitate early discharge and reduce the need to rehabilita- tion/nursing home services. richard.nicholas@btinternet.com